Green house gas emissions reporting and management in global top emitting countries and companies - Tauringana, Venancio; Moses, Olayinka (Advances in environmental accounting & management, 2023)
Human-induced climate change is one of the imminent threats to humankind in recent times. Climate change, exacerbated by the greenhouse gas (GHG) in the atmosphere has consequential effects on the social and environmental outcome of human health, clean air, sufficient food, safe drinking water and secure shelter. In extreme circumstances it has resulted in the loss of human life, damage to property and displacement. As record numbers of hurricanes, wildfires and floods have occurred and millions of people have been forcibly displaced by weather-related events and extreme temperatures since 2008, this volume addresses vital issues pertinent to environmental accounting and management. Green House Gas Emissions Reporting and Management in Global Top Emitting Countries and Companies increases our understanding of GHG emissions and documents evidence for policy formulation aimed at reducing the accumulation of such emissions. The contributors consider a range of issues from across the globe: the nature and quantum of GHG emissions research published in top journals; the extent of GHG disclosures in China; impact of corporate governance mechanisms on GHG disclosures in US; board interlocks effect on GHG performance in India; the Paris Climate Agreement affect on climate disclosures in South Africa; and social factors influence in determining GHG emissions in the top 100 emitting countries. The Advances in Environmental Accounting & Management series aims to advance knowledge of the governance and management of corporate environmental impacts and the accounting involved.